Changes in 800 meter personal records for competitive female runners from high school to college - Stewart, H. E.; Phillips, N.; McnittGray, J. L. (ISBS Proceedings Archive (Michigan), 2021)
To advance understanding of improvements in running performance, changes in personal records (PR) from high school to college were compared. It was hypothesized that females competing in the 800m in college would improve PR times from high school to college, improvements would be different between athletic conferences, and modern statistical methods could differentiate trends in the relationship between high school and college PR. Data from female athletes competing in the 800m from three different athletic conferences (n=73) were gathered from published race results and 79.4% improved by at least 1s with no significant differences between conferences. A positive relationship exists between high school and college PRs. Knowledge of changes in running performance provides context when interpreting an individual`s improvements in running biomechanics over time.